2022
DOI: 10.3233/jad-215678
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Use of Sodium-Glucose Co-Transporter-2 (SGLT2) Inhibitors and Cognitive Function in a Longitudinal Study of Patients with Type 2 Diabetes

Abstract: Background: The association between sodium-glucose cotransporter-2 inhibitors (SGLT2i) use and cognitive function in type 2 diabetes remains unclear. Objective: Explore the association between SGLT2i and longitudinal changes in cognitive function in adults with type 2 diabetes (T2DM) and assessed the cognitive domains which were impacted by SGLT2i. Methods: We conducted a prospective cohort study of 476 patients aged 60.6±7.4 years with follow-up period up to 6.4 years. Data on SGLT2i use was derived from ques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“… 45 Sodium‐glucose cotransporter 2 (SGLT2) inhibitors have shown improved cognitive function with both short‐term and long‐term usage. 46 , 47 The benefits of SGLT2 are believed to be an inhibition of the pro‐inflammatory pathway and a reduction in cerebrovascular disease risk. 48 There are limited data regarding cognitive function with meglitinides, α‐glucosidase inhibitors.…”
Section: Diabetes Mellitus and Psci /Post‐stroke D...mentioning
confidence: 99%
See 1 more Smart Citation
“… 45 Sodium‐glucose cotransporter 2 (SGLT2) inhibitors have shown improved cognitive function with both short‐term and long‐term usage. 46 , 47 The benefits of SGLT2 are believed to be an inhibition of the pro‐inflammatory pathway and a reduction in cerebrovascular disease risk. 48 There are limited data regarding cognitive function with meglitinides, α‐glucosidase inhibitors.…”
Section: Diabetes Mellitus and Psci /Post‐stroke D...mentioning
confidence: 99%
“…A meta‐analysis showed a lower risk of dementia in comparison with other oral hyperglycemic agents (OHA) for DPP‐4 inhibitor but not glucagon‐like peptide 1 receptor agonists (GLP‐1 RA) 45 . Sodium‐glucose cotransporter 2 (SGLT2) inhibitors have shown improved cognitive function with both short‐term and long‐term usage 46,47 . The benefits of SGLT2 are believed to be an inhibition of the pro‐inflammatory pathway and a reduction in cerebrovascular disease risk 48 .…”
Section: Diabetes Mellitus and Psci/post‐stroke Dementia (Psd)mentioning
confidence: 99%
“…Carmen et al found that empagliflozin reduced vascular damage and cognitive impairment in a mixed murine model of Alzheimer's disease and type 2 diabetes (48). However, we have little information on how SGLT2 inhibitors affect cognitive decline in clinical diabetes (49). Serena et al found that a SGLT2 inhibitor was positively associated with better cognitive scores in a cohort of patients with diabetes (50).…”
Section: Discussionmentioning
confidence: 99%
“…And a prospective study shows significant beneficial effects of the EMP on cognitive in frail older adults with diabetes (Mone et al, 2022). In addition, SGLT2I's ≥ 3 years use is related to the improvement of cognitive scores (Low et al, 2022). According to the existing evidence, longterm use of SGLT2i can improve cognitive function, especially for elderly diabetics.…”
Section: Sglt2 Inhibitorsmentioning
confidence: 99%
“…ClinicalDPP-4i is associated with low amyloid burden and favorable long-term cognitive outcome in diabetic patients with ADCI, sitagliptin's improvement of AD patient MMSE scores, vildagliptin to treatment improves the cognitive function of the older patients with T2DMIsik et al, 2017;Ates Bulut et al, 2020; Jeong et alClinical Long-term use of SGLT2i can improve cognitive function, especially for elderly diabeticsWium-Andersen et al, 2019;Mui et al, 2021;Low et al, 2022; Mone et al, 2022 …”
mentioning
confidence: 99%